The art of comics : a philosophical approach - Meskin, Aaron; Cook, Roy T., 1972- (Malden, MA : Wiley-Blackwell, 2012)
"The Art of Comics is the first-ever collection of essays published in English devoted to the philosophical topics raised by comics and graphic novels. In an area of growing philosophical interest, this volume constitutes a great leap forward in the development of this fast expanding field, and makes a powerful contribution to the philosophy of art. The first-ever anthology to address the philosophical issues raised by the art of comics. Provides an extensive and thorough introduction to the field, and to comics more generally. Responds to the increasing philosophical interest in comic art Includes a preface by the renowned comics author Warren Ellis. Many of the chapters are illustrated, and the book carries a stunning cover by the rising young comics star David Heatley "--
pt. One Nature and Kinds of Comics -- 1. Redefining Comics / John Holbo -- 2. Ontology of Comics / Aaron Meskin -- 3. Comics and Collective Authorship / Christy Mag Uidhir -- 4. Comics and Genre / Catharine Abell -- pt. Two Comics and Representation -- 5. Wordy Pictures: Theorizing the Relationship between Image and Text in Comics / Thomas E. Wartenberg -- 6. What's So Funny? Comic Content in Depiction / Patrick Maynard -- 7. Language of Comics / Darren Hudson Hick -- pt. Three Comics and the Other Arts -- 8. Making Comics into Film / Henry John Pratt -- 9. Why Comics Are Not Films: Metacomics and Medium-Specific Conventions / Roy T. Cook -- 10. Proust's In Search of Lost Time: The Comics Version / David Carrier.
Includes bibliographical references and index.
Print version record.
Keywords: Comic books, strips, etc -- History and criticism; Philosophy in literature; PHILOSOPHY -- Aesthetics; Comic books, strips, etc; Philosophy in literature; Comic; Electronic books; Criticism, interpretation, etc; Electronic books